2013
DOI: 10.1111/bph.12301
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with resveratrol attenuates sublesional bone loss in spinal cord‐injured rats

Abstract: BACKGROUND AND PURPOSESublesional osteoporosis predisposes individuals with spinal cord injury (SCI) to an increased risk of low-trauma fracture. The aim of the present work was to investigate the effect of treatment with resveratrol (RES) on sublesional bone loss in spinal cord-injured rats. EXPERIMENTAL APPROACHComplete SCI was generated by surgical transaction of the cord at the T10-12 level. Treatment with RES (400 mg·kg −1 body mass per day −1 , intragastrically) was initiated 12 h after the surgery for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…SCI typically throws the normal functioning of Central Nervous System (CNS) and adjoining tissues into a haywire, as is evident from our study and several others [3] , [4] , [22] [29] , [36] . Two perspectives emerge in this scenario: the off-balance situation of the CNS pathophysiology and the start and progression of efforts to bring back homeostasis and repair.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…SCI typically throws the normal functioning of Central Nervous System (CNS) and adjoining tissues into a haywire, as is evident from our study and several others [3] , [4] , [22] [29] , [36] . Two perspectives emerge in this scenario: the off-balance situation of the CNS pathophysiology and the start and progression of efforts to bring back homeostasis and repair.…”
Section: Discussionsupporting
confidence: 69%
“…Iron homeostasis [28] and blood coagulation pathways are also active during this phase. Administration of Resveratrol in SCI rats has shown upregulation of IGF-1 and Wnt1 mRNA indicating the involvement of insulin receptor signalling and Wnt pathways in post SCI pathophysiology [29] . tRNA transcription, which is a perturbed pathway in our study, probably points towards increased protein synthesis and has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol treatment was shown to decrease edema and inflammatory cytokine release (specifically IL-1β, IL-10, TNFα, and myeloperoxidase) after SCI in rats (Liu et al, 2011). Clinical studies showed that SCI patients suffer sub-lesion bone loss (Kocina, 1997), and resveratrol treatment prevents IL-6 and MDA levels leading to increased genesis of osteoblasts and osteoclasts in an experimental rat model of SCI (Wang et al, 2013). …”
Section: Anti-inflammatory Properties Of Resveratrolmentioning
confidence: 99%
“…The beneficial effect of cAMP on bone has been suggested by the findings in several systems [ 2 , 21 24 ]. Resveratrol which acts as a PDE inhibitor to activate cAMP signaling improves age-related metabolic syndromes [ 21 ] while it attenuates bone loss in vivo [ 22 , 23 ]. Most cannabinoid receptor antagonists activate cAMP production and mice with type 1 cannabinoid receptor deficiency exhibit increased peak bone mass due to reduced bone resorption [ 24 ].…”
Section: Discussionmentioning
confidence: 99%